Ways of Viewpoint Focalization in Hrant Matevosyan’s Novella “Hangover” - SHASHIKYAN, GRIGOR (Bulletin of Yerevan University B: Philology, 2021)
One of the basic concepts of narratology is the point of view. In the 1980s the term focalization, which was brought in use by G. Genette, became widely popular. It implied the restriction of the scope as compared to omniscience. Focalization has three degrees; zero, internal and external. These three can be presented simultaneously in some works, thus providing rhythmic and informational variation. A remarkable example of the simultaneous implementation of the three focalisation degrees in modern Armenian literature is the novella “Hangover” by Hrant Matevosyan, where the narrator conveys various information